Impact of COVID-19 pandemic on diagnosis and treatment access of patients with viral hepatitis in Turkey - Eser, Fatma; Güner, Rahmet; Gürbüz, Yunus; Akdoğan, Meral; Bilgiç, Zeynep; Korkmaz, Nesibe; Arı, Derya; Şanlıdağ, Gamze; Kesim Uçar, Şengül; Düzenli, Tolga; Yamazhan, Tansu (The Journal of Infection in Developing Countries, 2023)
Introduction: We aimed to evaluate access to diagnosis, treatment and follow-up in patients with viral hepatitis during the COVID-19 pandemic. Methodology: Patients who started treatment for hepatitis B and hepatitis C were included in the study and analyzed in two periods: before-pandemic and during-pandemic. Indication for treatment and frequency of laboratory follow-up was obtained from hospital records. A telephone survey was administered to evaluate treatment access and compliance. Results: Four centers with 258 patients were included in the study. Of these 161 (62.4%) were male, median age was 50 years. The number of patients, admitted to outpatient clinics was 134647 in the before-pandemic period and 106548 in the during-pandemic period. Number of patients who started treatment for hepatitis B were significantly high during-pandemic period compared with before-pandemic (78 (0.07%); 73 (0.05%) respectively; p = 0.04). The number who received treatment for hepatitis C was similar in both periods: 43 (0.04%); 64 (0.05%), respectively (p = 0.25). Prophylactic treatment for hepatitis B, due to immunosuppressive agents was significantly higher in during-pandemic period (p = 0.001). In the laboratory follow-ups at 4th, 12th and 24th weeks of treatment, worse adherence was detected in during-pandemic (for all p < 0.05). Access to treatment and compliance of all patients was over 90% and did not differ in the two periods. Conclusions: During-pandemic, hepatitis patients' access to diagnosis, treatment initiation and follow-up had worsened in Turkey. The health policy implemented during the pandemic had a positive impact on patients' access to and compliance to treatment.